Enhancing targeted delivery and efficacy of PEGylated liposomal doxorubicin with liposomal minoxidil: comprehensive in silico, in vitro, and in vivo tumor model studies - Vahideh Mohammadzadeh; Leila Arabi; Seyedeh Maryam Hosseinikhah; Mohammad Mashreghi; Fatemeh Kalalinia; Neda Mostajeran; Mohammad Reza Zirak; Farzin Hadizadeh; Mojgan Nejabat; Hossein Kamali; Niloufar Rahiman; Mahmoud Reza Jaafari (Drug Delivery, 2025)
The therapeutic efficacy of nanoparticle (NP)-encapsulated cytotoxic drugs has remained limited by poor penetration into solid tumors. To address this challenge, we developed a novel strategy using minoxidil-loaded nanoliposomes (Lip-MXD) to induce tumor vasodilation and enhance the delivery of PEGylated liposomal doxorubicin (PLD). We developed a remote loading method utilizing a calcium acetate gradient to encapsulate MXD into liposomes, achieving a high MXD encapsulation efficiency (87%). The resulting Lip-MXD formulation displayed an average particle size of 111 nm, a polydispersity index of 0.05, and a zeta potential of −15.7 mV. Pretreatment with Lip-MXD demonstrated multifunctional effects. It significantly downregulated CLDN-1 expression, improving NP penetration into advanced, fibrotic tumors. The stability of interaction between CLDN-1 and MXD was confirmed by molecular dynamics (MD) simulation. Immunohistochemistry and gene expression analyses in mouse models of colorectal (CRC) and pancreatic (PCa) cancers revealed that Lip-MXD administration significantly reduced the number of tumor-associated stromal cells. Furthermore, Lip-MXD mitigated tumor hypoxia and substantially enhanced PLD permeability within the dense microenvironment of desmoplastic tumors through its vasodilatory effects. A single dose of PLD following Lip-MXD pretreatment exhibited significant antitumor activity, resulting in a prolonged survival rate of 60% in the Lip-MXD+PLD-treated group in CRC models. In nude mice bearing PCa, the Lip-MXD+PLD-treated group achieved a significant reduction in tumor volume compared to the PLD group over a 14-day evaluation period. This MXD liposomal formulation offers a promising method to overcome tumor penetration, enhance NP delivery and improve therapeutic outcomes in CRC and PCa cancers, meriting further investigation.